The dark side of sport: managerial bullying and harassment challenges in different types of sports - Vveinhardt, Jolita; Fominienė, Vilija Bitė; Andriukaitienė, Regina (Journal of Business Economics and Management, 2020)
Bullying and harassment are the dark side of sport, not open to spectators and often ignored by coaches and leaders. Therefore, the research aim is to identify prevalence of bullying and harassment in Lithuanian organized sport with regard to individual, combat and team sports, highlighting measures/actions used to manage these phenomena. Survey research uses quantitative research strategy. The study involved 1440 organized sports athletes representing all sports types. The prevalence of bullying actions with regard to separate type of sports was identified: in individual sports (9.8%), in combat sports (8.5%), and in team sports (7.3%). The analysis by four specific actions has shown that athletes experienced most of such actions in combat sports (20%); almost half less, in team sports (10.8%) and individual sports (10.1%). The results of the study show a lack of bullying and harassment intervention and of comprehensive complaint submission procedures, while coaches particularly often ignore athletes’ negative behaviour. The article discusses managerial causes of bullying and harassment in the sports organization, presenting a holistic view of the phenomenon, including the forms of violence that have been little studied so far. This will help leaders to carry out prevention and intervention activities the specificity of which comes to prominence depending on the types of sports.